Richard Barr : the playwright's producer - Crespy, David Allison (Theater in the Americas., 2013)
In this book, the author investigates the career of one of the theatre's most vivid luminaries, from his work on the film and radio productions of Orson Welles to his triumphant - and final - production of Stephen Sondheim's Sweeney Todd: The Demon Barber of Fleet Street. Explored in detail along the way are the producer's relationship with playwright Edward Albee, whose major plays such as A Zoo Story and Who's Afraid of Virginia Woolf Barr was the first to produce, and his innovative productions of controversial works by playwrights like Samuel Beckett, Terrence McNally, and Sam Shepard.